BUDGETARY POLICY IN THE EUROPEAN UNION UNDER GEOECONOMIC UNCERTAINTY: TRENDS, CHALLENGES, AND THE 2024 REFORM OF THE STABILITY AND GROWTH PACT - S. O. Yakubovskiy (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu, 2025)
The article explores the evolution and transformation of budgetary policy in the European Union (EU) in the context of growing geoeconomic uncertainty, with a particular focus on the period from 2013 to 2024. The research is motivated by two major external shocks – the COVID-19 pandemic and Russia’s full-scale war against Ukraine – which have revealed significant weaknesses in the EU’s pre-existing fiscal governance framework and necessitated a comprehensive revision of the Stability and Growth Pact (SGP). The study addresses how these crises exposed asymmetries in fiscal responses and capacities across member states, leading to divergent recovery trajectories and highlighting structural imbalances in the Union's fiscal architecture.